Does a 'musical' mother tongue influence cry melodies? A comparative study of Swedish and German newborns. (June 2019) - Prochnow, Annette; Erlandsson, Soly; Hesse, Volker; Wermke, Kathleen
The foetal environment is filled with a variety of noises. Among the manifold sounds of the maternal respiratory, gastrointestinal and cardiovascular systems, the intonation properties of the maternal language are well perceived by the foetus, whose hearing system is already functioning during the last trimester of gestation. These intonation (melodic) features, reflecting native-language prosody, have been found to shape vocal learning. Having had ample opportunity to become familiar with their mother's language in the womb, newborns have been found to exhibit salient pitch-based elements in their own cry melodies. An interesting issue is whether an intrauterine exposure to a maternal pitch accent language, such as Swedish, in which emphatic syllables are pronounced typically on a higher pitch relative to other syllables will affect newborns' cry melody (fundamental frequency contour). The present study aimed to answer this question by quantitatively analysing and comparing the melody structure in 52 Swedish compared with 79 German newborns. In accordance with previous approaches, cry melody structure was analysed by calculating a melody complexity index (MCI) expressing the share of cries exhibiting two or more (well-defined) arc-like substructures uttered during the recording sessions. A low MCI reflects a dominance of cries with a 'simple', i.e. single-arc melody. A significantly higher MCI was found in the Swedish infant group, which further corroborates the assumption that the well-known foetal sensitivity for musical (melodic) stimuli seems to shape infants' cry melody.